Comparative Morphological Studies of Adrenal glands in Large white Yorkshire Pigs reared at Low and High altitudes in Kerala - S. Patgiri,; Rajani, C.V.; Surjith, K.P.; H.S. Patki,; Leena, C.; Indu V. Raj, (Indian Journal of Veterinary Anatomy, 2025)
The present study was conducted to record the topographical and morphologic features of the adrenal glands in 24 ten-month-old Large White Yorkshire pigs of either sex reared at low-altitude and high-altitude regions of Kerala. Adrenal glands were positioned either cranio-medially or entirely medially to the kidneys. The left adrenal was elliptical, whereas the right was elongated. The average weight and length of adrenals did not reveal any significant difference between the male animals reared at low and high altitudes and between the females reared at low and high altitudes. However, within the same altitude, the female groups had heavier right and left adrenal glands than the corresponding male groups.